TAFWÎD METHOD IN UNDERSTANDING MUTASHÂBIHÂT VERSES - Halimah B (UIN Sunan Kalijaga Yogyakarta, 2020)
Mutashâbihât verse is a verse that has a vague meaning. This vagueness can occur in terms of lafaz, or in terms of meaning, or in terms of lafaz and their meaning. In the existing debate, this paper aims to examine the methods used by scholars in understanding the mutashabihat verses. (a) How is the analysis of the interpretation of scholars in understanding the mutashâbihât verses? (b) What factors cause them to disagree? This paper is built from data collected through library research by tracing sources that relate directly to the theme. This paper uses the approach of interpretation and science. This paper shows that scholars use two methods in understanding mutashabihat verses. First; ta’wil method, they tend to understand the letter waw as waw ‘ataf in the fragment of verse wa al-rasikhuna fi al-’ilm (Q.S.Ali Imran (3): 7), which connects the previous sentence, the connotation is that Allah and the people are firmly grounded in knowledge know the definite meaning. Second; tafwid method, they tend to understand the letter waw as waw al-isti’naf functions as mubtada’ which is a new sentence. The connotation is to give its definite meaning to Allah alone and to those whose knowledge is profound in their faith. Some mutashabihat verses can be identified through scientific theory.